Do Habits of Mind and Cognitive Style Affect Critical Thinking Ability of High School Students? - Yohana Dwi Kristiani Sinaga; Elly Arliani (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2024)
This research aims to analyze the influence of habits of mind and cognitive style (field dependent and field independent) on the critical thinking ability of high school students. This research employs a mixed-method approach with an explanatory sequential design and a QUAN → qual model. The population consists of all 11th-grade high school students in Sintang Regency, West Kalimantan Province, with a sample of 385 students and 19 students serving as interview informants. The instruments used include a critical thinking ability test, habits of mind questionnaire, GEFT, and interview guidelines. The analysis techniques employed are descriptive analysis, inferential analysis, and qualitative analysis based on Miles & Huberman. The results show that habits of mind and cognitive style simultaneously have a significant influence on critical thinking ability. Furthermore, based on the coefficient of determination, it is found that habits of mind and cognitive style together have the power to explain critical thinking ability. The implication is that teachers need to adjust learning strategies based on students' cognitive styles and develop habits of mind to improve their critical thinking skills.